رأس المال الفكري وأثره في تصميم المنتج: دراسة استطلاعية في الشركة العامة لصناعة الادوية و المستلزمات الطبية/نينوى - محمد منيب محمود (PROSPECTIVE RESEARCHES, 2023)
This research tries to explain the effects of intellectual capital on product design in the state Company for drug industries and medical appliances/Nineveh. The product design and development can be considered as a strategic process because it might lead the company to failure or enhance its competitiveness position in marketplace. The process of design requires experience, knowledge and suitable intellectual capabilities, in addition to the organizational elements and components such as kinds of technologies used, work procedures and constantly working to establish best relations with the external parties that trade with it and understand their needs and desires in order to satisfy it well and do every thing that could enable the company to make all tangibles and intangible resources working for producing pharmaceutical products that satisfy its customers needs and make profits at the same time. The research concludes that there is a significant correlation and regression for intellectual capital in product design and according to the conclusions, some recommendations are presented.